Thainema gen. nov. (Leptolyngbyaceae, Synechococcales): A new genus of simple trichal cyanobacteria isolated from a solar saltern environment in Thailand - Rasouli-Dogaheh, Somayeh; Komárek, Jiří; Chatchawan, Thomrat; Hauer, Tomáš (PloS one, 2022)
Simple trichal types constitute a group of cyanobacteria with an abundance of novel, often cryptic taxa. Here, we investigated material collected from wet surface-soil in a saline environment in Petchaburi Province, central Thailand. A morphological comparison of the isolated strain with similar known species, as well as its phylogenetic and species delimitation analyses based on the combined datasets of other related organisms, especially simple trichal cyanobacteria, revealed that the material of this study represented an independent taxon. Using a multifaceted method, we propose that this material represents a new genus, Thainema gen. nov., belonging to the family Leptolyngbyaceae, with the type species Thainema salinarum sp. nov. This novel taxon shares similar ecological habitats with strains previously placed in the same lineage.
Keywords: Thajsko; Bacterial Typing Techniques; sinice; Cyanobacteria; Thailand; techniky typizace bakterií; ekosystém; Ecosystem